“Fairy Rings” of Participation: The "invisible” network influencing participation in online communities - Makriyannis, Elpida; DeLiddo, Anna (Proceedings of the International Conference on Networked Learning, 2010)
Individuals participate in many different ways in online communities. There is an extensive body of research describing participation as a key metaphor in communities of practice and stressing that participatory mobility is influenced by underground multidirectional activities, directed away from the notion of periphery to the centre practices and taking the shape of expansive swarming and multidirectional pulsations. This article describes an ongoing observational study proposing a model that attempts to determine how users participate in online communities and what influences them to alter the way in which they participate. We performed daily observations on user participatory behaviour in 50 online communities using public domain – anonymous data available in the communities. The specific communities were selected because they are related to learning and support learning activities within their networks. The data observations collected were analysed using Compendium, a hypermedia knowledge mapping and sense-making tool, to represent and structure the data, make complex cross data queries, test hypotheses and build representation of real examples to support our claims. Initial findings indicate that users connect, participate, contribute and collaborate on a shared objective, transferring information and pooling knowledge within and between communities in four different modes. During their online journey, users switched between modes of participation or even remained in one specific mode, implying that the way in which users participate in an online community is not just related to the mode of participation and the level of engagement with the community but it is also due to hidden reasons or motivations, an invisible network of interactions of elements that affect the willingness of the user to participate. This layer is not immediately evident in the user actions but can be inferred by analysing user reactions. It is argued that user participation in online communities occurs in two layers; the “visible” layer of participation with the different modes; and the “invisible” layer of element interactions, similar to formations observed in nature when a radically spreading underground network of fungi activity results in a ring or arc formation of mushrooms, also known as a “fairy ring”. These underground multidirectional activities influence participation and participatory mobility. Following an open scientific inquiry approach and an open research paradigm we plan to share these observations with a wider audience of practitioners, researchers and theorists for all to test or contest our arguments, and to enrich, question, or support our model.